Pengaruh Latihan Aerobik terhadap Peningkatan Kadar High Density Lipoprotein pada Atlet Aerobic Gymnastics - Ali, Mohammad Arif (Universitas Negeri Semarang, 2013)
The purpose of this study was to determine the effect of aerobic exercise on the increased levels of high-density lipoprotein in the blood of athletes aerobic gymnastics Central Java province. Experimental research methods research design with one group pretest-posttestwith treatment form of aerobic exercise with intensity of 75-85% of DN Max, duration and frequency of exercise 4560 minutes of exercise 3-5 times per week for 8 weeks. The population in this study are all athletes aerobic gymnastics Central Java province. Data retrieval technique with purposive sample, obtained 6 samples aerobic gymnastics athletes. This study variables aerobic exercise and levels of high density lipoprotein (HDL) (mg / dl). To analyze differences in changes in HDL cholesterol levels in the two groups used the T test analysis.There are significant differences in the levels of HDL between before and after exercise aerobikkelompok, t> t table, ie 4663> 2571. Aerobic exercise can increase levels of high-density lipoprotein in the blood of athletes aerobic gymnastics Central Java province at 3:34 mg / dl or 7:47%. Conclusion: Aerobic exercise effect on increasing levels of high density lipoprotein.